Pengaruh Faktor Kompetensi Terhadap Kinerja Individu di Perusahaan Agroindustri Go Public - Yosep Rizal; Musa Hubeis; Sjafri Mangkuprawira; Agus Maulana (Institut Pertanian Bogor, 2013)
Challenges facing companies in the era of globalization characterized by the occurrence of free trade. This study describes the competencies to create individual performance for the company to grow and to develop by using SEM to investigate the factors influencing the individual competencies at go public agroindustry. Data collection was performed according to the variables in this study by the number of 202 respondents in the sample with stratified random sampling. Respondents include employees at the level of general manager, manager, superintendent and supervisor. The results showed that there are five factors effecting competency, namely commitment, conceptual thinking, operational, achievement and influence. In order for optimal achievement of individual performance in the company's agroindustry, it is to be supported other characteristics, namely motivation, job satisfaction and engagement. The findings from this study are expected to be useful in the assessment of competencies of human resources, especially in the agroindustry companies to be used in the process of recruitment, placement, promotion and compensation to employees in a fair, effective way to support the corporate strategy